Chemical transfer of dissolved organic matter from surface seawater to sea spray water-soluble organic aerosol in the marine atmosphere. Issue 1 (December 2018) - Miyazaki, Yuzo; Yamashita, Youhei; Kawana, Kaori; Tachibana, Eri; Kagami, Sara; Mochida, Michihiro; Suzuki, Koji; Nishioka, Jun
Abstract It is critical to understand how variations in chemical composition in surface seawater (SSW) affect the chemistry of marine atmospheric aerosols. We investigated the sea-to-air transfer of dissolved organic carbon (DOC) via cruise measurements of both ambient aerosols and SSW in the Oyashio and its coastal regions, the western subarctic Pacific during early spring. Sea spray aerosols (SSAs) were selected based on the stable carbon isotope ratio of water-soluble organic carbon (WSOC) (δ13 CWSOC ) and concentrations of glucose as a molecular tracer in marine aerosols together with local surface wind speed data. For both SSA and SSW samples, excitation-emission matrices were obtained to examine the transfer of fluorescent organic material. We found that the ratios of fluorescence intensity of humic-like and protein-like substances in the submicrometer SSAs were significantly larger than those in the bulk SSW (~63%). This ratio was also larger for the supermicrometer SSAs than for the SSW. The results suggest significant decomposition of protein-like DOC on a timescale of <12–24 h and/or preferential production of humic-like substances in the atmospheric aerosols regardless of the particle size. This study provides unique insights into the complex transfer of DOC from the ocean surface to the atmosphere.